A audiência de custódia como instrumento de inibição da tortura: um estudo dessa iniciativa na cidade de São Paulo - Pereira, Bianca Vettorazzo Brasil (2019)
The military dictatorship established in 1964 in Brazil used torture as an institutionalized way against its political opponents. The democratic reopening took place with the amnesty of the torturers too, who were not obliged to make an apology to the Brazilian society for their actions. This fact generated a collective repression in the Brazilian society that made the practice of torture to continue to be used daily and, therefore, the impunity of this crime was the rule, not the exception. For these reasons the establishment of institutes like the custody hearing, which has as one of the functions to inhibit the use of torture at the time of arrest, becomes of fundamental importance for the effectiveness of the prohibition of torture in the country. As observed in the present work, this institute has not been effective in combating torture, either for practical reasons like the presence of the police during the hearing and forensics, or for cultural reasons of connivance if violence that are present in all actors in custody hearing This fact means that the custody hearing is not fulfilling in its role of combating the use of torture at the time of arrest and assisting in the conviction of those responsible for such practice. In a quantitative research carried out for this work on the TJ / SP website, it was observed that no one of the proceedings against torture in the city of São Paulo are the result of the custody hearing. Thus, the custody hearing, as it has been held in the city of São Paulo, was shaped so as not to change the foundations that are fundamental to the use of torture until the present day